PENEGAKAN HUKUM TINDAK PIDANA PROSTITUSI DI WILAYAH KEPOLISIAN RESORT KOTA SIDOARJO - Hidayat, Rizaldy Ari; Mardijono, Adianto (Gapenas Publisher, 2024)
Human trafficking is a crime committed by recruiting, delivering, or accepting people by force, fraud, with the aim of utilizing victims for profit. This study aims to determine the law enforcement of Sidoarjo City Resort Police in preventing and eradicating the crime of trafficking in persons of prostitution and efforts to overcome it. The results of this study found that law enforcement of human trafficking in prostitution in Sidoarjo jurisdiction has many internal and external obstacles so that the Sidoarjo City Resort Police made socialization efforts, formed a special team and empowered police officers and collaborated with the community and government